Cytokines and chemokines expression in serum of patients with neuromyelitis optica - Ai, Nanping (Neuropsychiatr Dis Treat, 2019)
OBJECTIVE: To study the differences in immunopathogenesis based on chemokine profile in neuromyelitis optica patients positive for AQP4 antibodies or MOG antibodies. PATIENTS AND METHODS: We measured 52 cytokines/chemokines using ELISA in 59 serum samples, which were divided into three groups according to CBA results: HCs (n=16), AQP4+ (n=20) and MOG+ (n=23). The regression equation (R(2)>0.98) of the standard curve was calculated according to the standard concentration and the corresponding A value. And then the corresponding sample concentration was calculated according to the A value of the sample. RESULTS: Eleven of 52 measured serum cytokine/chemokines (CCL22/MDC, CCL13/MCP-4, CCL21/6Ckine, CCL27/CTACK, CCL8/MCP-2, CXCL14/BRAK, Contactin-1, Kallilrein 6/Neurosin, Midkine, VCAM-1 and Fas) were significantly different between MOG+ group and controls. Ten of 52 measured serum cytokine/chemokines (CCL1/I-309, CCL22/MDC, CCL28, CCL17/TARC, CCL27/CTACK, CXCL2/GRO beta, Contactin-1, Midkine, Chemerin and Synuclein-alpha) were significantly different between AQP4+ group and controls. There was no difference between serum AQP4+ and MOG+ groups for CC chemokines. All measured chemokines CXC except CXCL6/GCP-2 showed no significant differences in serum AQP4+ group compared to MOG+ group. However, there was significant difference between serum AQP4+ and MOG+ groups for C5/C5a and Midkine. C5/C5a and Midkine were significantly higher in AQP4+ group compared to MOG+ group (P<0.05). CONCLUSION: Our findings suggest that the differences of mean concentration in CXCL6/GCP-2, Midkine and C5/C5a probably reveal different immunologic mechanism between AQP4+ NMO and MOG+ NMO. This cytokine/chemokine profiling provides new insight into NMO pathogenesis associated with MOG antibody seropositivity and provides guidance to monitor inflammation and response to treatment in a way.